A New Pharmacologic Treatment for Nausea and Vomiting of Pregnancy. Issue 1 (February 2014) - Fantasia, Heidi Collins
Abstract Nausea and vomiting of pregnancy (NVP) affects up to 80 percent of pregnant women. This condition is usually self‐limiting, but the symptoms can be distressing and interfere with work, social activities and sleep. Symptoms can often be managed by diet and lifestyle changes, but these interventions may not be successful for everyone. In April 2013, the U.S. Food and Drug Administration approved doxylamine succinate 10 mg/pyridoxine hydrochloride 10 mg (Diclegis®) as the first medication to specifically treat NVP in more than 30 years. This article reviews the indications, dosage and nursing interventions associated with using doxylamine succinate/pyridoxine to treat NVP.